Peran Kompetensi Aparatur Pemerintah dalam Penerapan e-Accounting untuk Meningkatkan Akuntabilitas dan Efisiensi Pelaporan Keuangan di Kecamatan Krembangan dan Kecamatan Asemrowo Surabaya - Aliatus Nurrochmah; Dewi Sutjahayani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
The competence of government officials is a major factor in the successful implementation of e-Accounting in government agencies, particularly in the process of preparing financial reports based on Government Accounting Standards (SAP). This study aims to describe the role of official competence in the use of e-Accounting and how its implementation affects the accountability and efficiency of financial reporting in the Krembangan and Asemrowo districts of Surabaya. This study uses a qualitative approach through interviews, observations, and document reviews. The results show that the competence of officials still varies, especially in understanding accrual-based accounting, accuracy in data input, and the ability to operate system features. Although e-Accounting has improved accountability through documented and easily traceable transaction records, reporting efficiency has not been fully achieved due to differences in technical capabilities among employees and operational constraints of the system. Thus, skill improvement and continuous training are necessary so that the implementation of e-Accounting can support more effective, accurate, and compliant financial reporting.